Factors influencing lateral margin diagnosis challenges in Barrett’s esophageal cancer: a bicenter retrospective study in Japan - Ippei Tanaka; Shuhei Unno; Kazuki Yamamoto; Yoshitaka Nawata; Kimihiro Igarashi; Tomoki Matsuda; Dai Hirasawa (Clinical Endoscopy)
Background/Aims We aimed to clarify the clinicopathological characteristics and causes of Barrett’s esophageal adenocarcinoma (BEA) with unclear demarcation. Methods We reviewed BEA cases between January 2010 and August 2022. The lesions were classified into the following two groups: clear demarcation (CD group) and unclear demarcation (UD group). We compared the clinicopathological findings between the two groups. Furthermore, we measured the length and width of the foveolar structures, as well as the width of marginal crypt epithelium (MCE). Results We analyzed data from 68 patients with BEA, including 47 and 21 in the CD and UD groups, respectively. Multivariate analysis revealed long-segment Barrett’s esophagus (LSBE) as the sole significant risk factor for BEA (odds ratio, 12.17; 95% confidence interval, 2.84–47.6; p=0.001). Regarding pathological analysis, significant differences were observed in the length and width of the foveolar structure between cancerous and surrounding mucosa in the CD group (p=0.03 and p=0.00, respectively); however, no significant difference was observed in the UD group (p=0.53 and p=0.72, respectively). Nevertheless, the width of MCE in the cancerous area was significantly shorter than that in the surrounding mucosa in both groups (all, p<0.05). Conclusions LSBE is a significant risk factor for BEA in the UD group. The width of MCE may be an important factor in the endoscopic diagnosis of BEA.